2021
DOI: 10.5195/ijms.2021.894
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Recycled Eyeglasses: A Pilot Study at the Los Angeles County Department of Health Services

Abstract: Background: The cost of eyeglasses is variably covered by medical insurance and thus is a significant barrier for patients in lower socioeconomic classes. We wanted to evaluate the efficacy of Recycle Vision (RV) at LAC+USC Medical Center, a monthly clinic run by volunteer medical students that provides free donated eyeglasses. Methods: A convenience sample of 30 patients were surveyed from August 1, 2019 to December 31, 2019. Patients’ prescriptions were matched with available eyeglasses bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Results of this cross-sectional AFEDS trial suggest that there were approximately 1 of 7 individuals with an uncorrected refractive error and approximately 1 of 20 individuals with an unmet refractive need (5.4%) in a sample of African American individuals. These data suggest that given the relatively inexpensive and easy intervention of refraction and provision of refractive correction, it may be possible to reduce this leading cause of visual impairment in this vulnerable segment of the US population, assuming these individuals subsequently used the refractive correction habitually …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Results of this cross-sectional AFEDS trial suggest that there were approximately 1 of 7 individuals with an uncorrected refractive error and approximately 1 of 20 individuals with an unmet refractive need (5.4%) in a sample of African American individuals. These data suggest that given the relatively inexpensive and easy intervention of refraction and provision of refractive correction, it may be possible to reduce this leading cause of visual impairment in this vulnerable segment of the US population, assuming these individuals subsequently used the refractive correction habitually …”
Section: Discussionmentioning
confidence: 92%
“…These data suggest that given the relatively inexpensive and easy intervention of refraction and provision of refractive correction, it may be possible to reduce this leading cause of visual impairment in this vulnerable segment of the US population, assuming these individuals subsequently used the refractive correction habitually. [36][37][38][39]…”
Section: Discussionmentioning
confidence: 99%
“…Patients selected the reason for not obtaining glasses elsewhere from a predetermined list. All questions were verified by a previous free glasses clinic study [10].…”
Section: Primary Survey Methodologymentioning
confidence: 99%
“…A previous pilot study [10] has also assessed the immediate impact of free donated glasses clinic on 30 Los Angeles residents. Most patients (70%) indicated that cost was the most prevalent barrier.…”
Section: Introductionmentioning
confidence: 99%
“…1 Other accomplishments that are noteworthy in the journal's first decade of existence include the indexing of multiple publications in PubMed Central (PMC). 1,[5][6][7][8][9][10][11] Another major accomplishment can be appreciated when looking at the journal's success as it pertains to funding of the research that is published. Medical students under the mentorship of investigators with funding from the National Institute of Health (NIH) of the United States have specifically chosen the IJMS to publish their work.…”
Section: Introductionmentioning
confidence: 99%